Rarity and the Poetic: The Gesture of Small Flowers - Schweizer, Harold; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Rarity is a quality by which things flowers, leaves, light, sound fleetingly appear and disappear, leaving in their wake a resonance of something we just thought we had glimpsed. Each of the nine chapters in this book pursues such intimations of rarity in poetic ideas, images, and silences.
Keywords: Literature-History and criticism; Poetry and Poetics